Perceived impact of the COVID-19 pandemic on infection containment training and mental state of dental residents in China: A longitudinal study - Dai, Lina; Jiang, Dan; Wen, Qin; Zhang, Ximu; Song, Jinlin (Frontiers in Public Health, 2022)
Background COVID-19 has presented a challenge for dental settings and dental schools: how to continue providing dental care and maintain education during the pandemic while remaining healthy. We highlight the necessity of infection containment control training for dental residents and rethink the tasks of safeguarding trainees' health and cultivating their abilities to deal with public health crises in the future. This paper may also serve as a health policy reference for policy makers. Objective The study aimed to compare the formats, frequency, contents, emphasis, and test scores of infection containment control training pre- and post-pandemic. Besides, after the COVID-19 outbreak, we assessed the increased anxiety level, communication difficulties, and confidence of dental residents impacted by the pandemic. Methods A total of 251 dental residents in Stomatological Hospital of Chongqing Medical University were recruited to complete a questionnaire of their routine involvement in infection control training before and after the COVID-19 outbreak. A self-designed 10-point Likert scale was used to assess the increased anxiety level, communication difficulties, and confidence in facing with the future public health crisis impacted by the pandemic. Results After the outbreak, although more trainees chose online assessment than offline assessment, most of them (74.90%) still preferred in-person training rather than online training. Contents that trainees had been focusing on were affected by the COVID-19 outbreak. Thereafter, they were more inclined to learn crisis management. Over half of the participants (56.17%) participated in training more frequently after the outbreak. However, postgraduate students participated in training less frequently than others after the outbreak (p < 0.01). First-year trainees accounted for the majority in the population who emphasized considerably on infection control training and whose test scores had increased after the outbreak. In addition, the percentage of women scoring increasingly in post-pandemic assessment was significantly higher than that of men. In this study, the average increased anxiety level caused by COVID-19 was 5.51 ± 2.984, which was positively related to communication difficulties with patients caused by the pandemic. The trainees whose homes were located in Hubei Province showed higher increased anxiety levels (8.29 ± 2.93) impacted by the pandemic than the trainees from other provinces (p < 0.05). However, the former's confidence in coping with future public health crises was not significantly different from that of others (p > 0.05). Conclusions Owing to the impact of COVID-19, the contents that the trainees focused on, frequency, emphasis, and test scores of infection containment control training were changed. Some recommendations have been provided for policy makers to attach importance to crisis-based training to cultivate dental residents in the post-pandemic era.